Traumatic bilateral acetabular fracture secondary to high-energy trauma in healthy adults - Guy Romeo Kenmegne; Chang Zou; Yixiang Lin; Yijie Yin; Shenbo Huang; Yue Fang (BMC Surgery, 2024)
Abstract Background Bilateral acetabular fracture is a very rare presentation among the trauma patients, as the pattern and the degree of the forces required to fracture both acetabula is very unique. The primary purpose of this study is to report a series of adult patients presenting with post-traumatic bilateral acetabular fracture without any history of pathological or metabolic bone disease. Patients and methods In this retrospective study, 18 cases of traumatic bilateral acetabular fracture were included. There was predominance of both column (four patients on left and six on right) followed by anterior column (two patients left and four on right) and posterior wall (three patients left and right). They were treated surgically through open reduction and internal fixation. All cases were followed up for at least 13 months. Matta’s criteria were used for radiological evaluation on plain radiographs. Functional outcome was evaluated using the Merle d’Aubigne and postel score at final follow-up. Results No patients were lost during the follow-up period; there was one case of surgical site infection. There were three cases of postoperative osteoarthritis, one case of heterotrophic ossification, one case of persistent sciatic nerve palsy and one case of lateral femoral cutaneous nerve palsy. The radiological evaluation according to Matta’s criteria revealed anatomic reduction in 12 patients, imperfect reduction in three patients while other three patients had poor reduction. According to modified Merle d’Aubigne and Postel score, 10 cases were rated as excellent, five cases as good and three cases presented fair (one case) to poor (two cases) results. Conclusion We report an unusual case series of bilateral acetabular fracture successfully managed surgically with good clinical outcome. With the increasing incidence of route traffic accidents, such cases would probably be recurrent in the upcoming years.